High-strength and high-conductivity Cu-0.7Mg-0.1Ca alloy fabricated via heat treatment and severe plastic deformation - Kalhor, Alireza; Rodak, Kinga; Myalska-Głowacka, Hanna; Chmiela, Bartosz; Kuglarz, Karol; Schindler, Ivo; Radwański, Krzysztof; Kampik, Marian (Journal of Mining and Metallurgy, Section B: Metallurgy, 2025)
In this research, the effect of annealing in combination with severe plastic deformation (SPD) by the MaxStrain component of the Gleeble thermo-mechanical testing device on the microstructural characteristics, tensile behavior, and electrical conductivity of a Cu-0.7Mg-0.1Ca (wt%) alloy was investigated. The as-cast material was subjected to two treatments: annealing at 923 K for 15 min, followed by cooling in air, and annealing at 923 K for 75 min, followed by quenching in agitated water, which resulted in irregular and partially spheroidized Cu5Ca particles. Subsequent MaxStrain deformation resulted in a remarkable grain refinement by dynamic recrystallization (DRX), in which the annealed and quenched sample exhibited a higher DRX fraction than the annealed and air-cooled sample. As a result, the annealed and quenched samples showed a better synergy between strength and ductility, while these improvements were accompanied by only ~1% reduction in electrical conductivity. Accordingly, the present work demonstrated that annealing and subsequent SPD processing is as an effective method for processing high-strength and high-conductivity (HSHC) copper alloys.